Deliberate release of genetically modified plants into the environment in Slovenia - Zlata LUTHAR (Acta Agriculturae Slovenica)
Deliberate release of genetically modified higher plants (GMHPs) into the environment in Slovenia is regulated by the Law on the Management of Genetically Modified Organisms (ZRGSO) Ur. l. RS 23/2005 and 21/2010, III chapter. For each deliberate release of GMPs into the environment a license issued by the Ministry of Environment and Spatial Planning (MESP) must be acquired. The application or notification should contain a very accurate and complex description of the GMP, of the field where it will be released and of wider surroundings or environment. The application consists of Annex 2 with accessories: 1. Part A (technical data for the authorization of deliberate GMP release into the environment); 2. Part B (environmental risk assessment); 3. Application summary in Slovenian and English language) for the release of GMP into environment, which is transmitted to Brussels by MESP; 4. Extract from the Land Cadastre of the field to which the GMP will be released. The release procedure runs (till here) under the above mentioned Law, which has been in place for several years and which clearly defines that it is possible to release GMP in Slovenia. In the case of GM rice in 2011, the law applied till the site selection of the experiment. Here, the law was not sufficiently taken into account. It was prevailed by the regulation of Farmland and Forest Fund of the Republic of Slovenia and municipal decision, which was stronger than the national law and prevented the cultivation of GM rice in an area that is legally suitable for release of GMO into the environment. Rice is not grown in Slovenia and does not have wild ancestors or close relatives with whom it might mate. Nearest area of cultivation is in neighboring Italy, which is from potentially selected location in Slovenia more than 70 km away.